2017
DOI: 10.1007/s00436-017-5624-6
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma brucei: trypanocidal and cell swelling activities of lasalocid acid

Abstract: Chemotherapeutic treatment of human and animal trypanosomiasis is unsatisfactory because only a few drugs are available. As these drugs have poor efficacy and cause adverse reactions, more effective and tolerable medications are needed. As the polyether ionophore antibiotic lasalocid acid is used as medicated feed additive in cattle, the compound was tested for its trypanocidal and cytotoxic activity against bloodstream forms of Trypanosoma brucei and human myeloid HL-60 cells. The concentrations required of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…This mode of action differs from the mechanism of the anti-cancer activity of salinomycin reported to be the induction of apoptosis [53]. Interestingly, lasalocid acid has been found to induce a much faster cell swelling in trypanosomes than salinomycin and other polyether ionophores, and that the swelling was solely due to the influx of Na + cations [65]. Thus, it has been suggested that lasalocid acid may be directly applicable for the treatment of nagana disease, particularly as it is used in cattle as medicated feed additive ( Table 2)…”
Section: African Trypanosomiasismentioning
confidence: 71%
See 3 more Smart Citations
“…This mode of action differs from the mechanism of the anti-cancer activity of salinomycin reported to be the induction of apoptosis [53]. Interestingly, lasalocid acid has been found to induce a much faster cell swelling in trypanosomes than salinomycin and other polyether ionophores, and that the swelling was solely due to the influx of Na + cations [65]. Thus, it has been suggested that lasalocid acid may be directly applicable for the treatment of nagana disease, particularly as it is used in cattle as medicated feed additive ( Table 2)…”
Section: African Trypanosomiasismentioning
confidence: 71%
“…As the few commonly used and outdated drugs available to treat sleeping sickness patients have limited efficacy as well as adverse side reactions, novel and better tolerated therapeutic strategies are highly desirable. The results from very recently published studies have clearly shown that three carboxylic polyether ionophores -lasalocid acid, monensin and salinomycin ( Figure 1) -are interesting lead compounds for rational anti-trypanosomal drug development in this context [65][66][67]. Importantly, it has been shown that monensin and salinomycin inhibit the growth of culture-adapted bloodstream forms of T. brucei (clone 427-221a) in vitro at sub-micromolar concentration [66,67].…”
Section: African Trypanosomiasismentioning
confidence: 99%
See 2 more Smart Citations
“…All SAL precursors and their newly synthesized double-modified derivatives were evaluated for their in vitro activity against bloodstream forms of T. brucei and human myeloid HL-60 cell using the resazurin cell viability assay [28,29]. All compounds showed a dosedependent inhibitory effect on the growth of bloodstream-form trypanosomes ( Table 1).…”
Section: Anti-trypanosomal Activitymentioning
confidence: 99%